Minat dan Motivasi Pengunjung dalam Berolahraga di Gelanggang Olahraga Tri Lomba Juang - Nandika, Inanda Rizka; Mulyono, Aris (Indonesian Journal for Physical Education and Sport, 2023)
The aims of this research are to know visitors' interest and motivation in exercising at the GOR Tri Lomba Juang. The method used in this research is to apply a qualitative survey approach. Data collection techniques in research using polls, observations, and documentation. The instrument test results in this research used SPSS22 program validity check and reliability test. The method used for data analysis is the descriptive percentage analysis (DP). Based on the results of the study conducted with 100 respondents obtained data indicating that the interest of visitors to exercise based on willingness and environment is categorized very high with the results of the research percentage showed 88,5%, and the motivation of visitors in exercising based on physiological needs indicator also included in the very high category with the results of a research percentage of 89,93%. The average results of the research and motivation of visitors in the exercise at the GOR Tri Lomba Juang Semarang based on the age shows the results of the study is for the age of teenagers 66%, the age of adults 23%, and the elderly 11%. Conclusion of the research results and the motivation of visitors in the exercise at the GOR Tri Lomba Juang reach in very high category.